Development of the composition and technology of a combined gel for the treatment of osteoarthritis with a pharmacological rationale for the content of components - U. V. Nogaeva; Ju. M. Kotsur; E. V. Flisyuk; D. Yu. Ivkin; E. D. Semivelichenko; I. A. Titovich; I. A. Narkevich; V. G. Antonov (Разработка и регистрация лекарственных средств, 2021)
Introduction. Osteoarthritis (OA) is the most common joint disease that affects more than 10 % of the world's population. More than 600 000 people are diagnosed for the first time each year, but these data do not reflect the true prevalence of the disease, since not all patients seek help from hospitals [1, 2].Aim. Pharmaceutical development of the composition and technology of a gel based on meloxicam, a purine derivative and an immunomodulating component for the treatment of OA with pharmacological substantiation of the content of active substances.Materials and methods. A combination of three active pharmaceutical substances was studied: a non-steroidal anti-inflammatory drug – meloxicam, a purine derivative and an original immunomodulator M. Sodium alginate, natrozole and xanthan gum were considered as gelling agents. Were identified two technological modes of obtaining a gel base. The concentrations of active substances were selected based on the results of preclinical studies. OA was modeled by the combined administration of 0.1 ml of a mixture of Freund's complete adjuvant with a 10 % talc suspension in isotonic sodium chloride solution in a ratio of 1 : 10 into the hock (tarsus) joint cavity. The criteria for choosing the optimal composition of the gel were the size of the damaged joint, exercise tolerance and the histological picture in comparison with intact and control animals. For quantitative data, sample mean values (M) and standard deviations (SD) were calculated. The results corresponded to the laws of normal distribution, statistical processing was carried out using one-way analysis of variance (One-Way ANOVA) using the GraphPad Prism 8.0.2 software, USA at the level of statistical significance of differences p < 0,05 и p < 0,001.Results and discussion. The composition was developed and the technology of the topical dosage form based on sodium alginate was proposed. Preclinical data indicate that the highest efficacy is achieved when using a formulation containing 3 % purine derivative, 5 % immunomodulator M and 0.5 % meloxicam. The developed composition for the effectiveness of suppressing the symptoms of OA showed results that exceeded the reference drug.Conclusion. An original combined agent for the treatment of OA has been developed. Due to the selected component composition, with greater efficiency, it was possible to reduce the dosage of meloxicam to 0.5 %, and the use of sodium alginate as a gelling agent contributed to the prolongation of the action of the gel and the subsequent reduction in the number of applications.